Implications Due to Challenges to Food Security in Malaysia - Zulkifli, Mohd Farhan bin; Rahman, Azrul Azlan Abd; Zulkifli, Noraini; Yasid, Amer Fawwaz Mohamad; Mat, Bakri; Alias, Mohd Salman bin (Journal of Ecohumanism, 2025)
The issue of food security encompasses challenges related to production, distribution, and accessibility of nutritious food. In Malaysia, food security is increasingly threatened due to reliance on imports, declining agricultural productivity, and income inequality. In 2023, food imports reached RM78.7 billion, indicating heavy dependence on global markets. Population growth, expected to reach 42 million by 2050, exacerbates the demand for food, creating further stress on the nation’s food systems. This study employed a qualitative methodology to analyze factors impacting Malaysia’s food security, focusing on secondary data from academic and institutional sources. Document analysis was used to examine existing policies and data on food security and its implications. Key findings highlight that food insecurity in Malaysia leads to hunger, malnutrition, and related health issues, such as childhood stunting and obesity. The COVID-19 pandemic significantly worsened these conditions, with 30% of the population estimated to experience food insecurity. Environmental factors, including climate change, deforestation, and resource overuse, further challenge food production. Additionally, global disruptions, such as the Russia-Ukraine conflict, have escalated costs and strained supply chains. The study concludes that addressing Malaysia’s food security requires a holistic approach, integrating sustainable agricultural practices, reducing dependency on imports, and strengthening local food systems. Collaborative efforts between governments, private sectors, and international organizations are essential to ensure an equitable and sustainable food future. This research underscores the urgent need for policy reforms and strategic planning to safeguard Malaysia’s food security amidst growing global and local challenges.